Seed removal by lizards and effect of gut passage on germination in a columnar cactus of the Caatinga, a tropical dry forest in Brazil. (December 2016) - Gomes, V.G.N.; Meiado, M.V.; Quirino, Z.G.M.; Machado, I.C.
Abstract: The seed disperser's effectiveness relates to the qualitative and quantitative components of seed dispersal processes in terms of frequency, dispersal distance and seed germination. This study recorded Tropidurus semitaeniatus lizards acting as primary seed dispersers of Pilosocereus gounellei, a columnar cactus for which fruit morphology suggests ornitochory is its primary seed dispersal mode. We evaluated the effectiveness of seed dispersal by this lizard by experimentally assessing their qualitative and quantitative components. In 54 h of focal observations, lizards made 44 visits during different day time, with a mean dispersal distance of 6.50 ± 3.0 m. We collected (n = 96) intact and viable consumed seeds from 9 faecal samples. We conducted germination experiments with these seeds and compared the results to two other treatments: washed seeds and control. Passage through the lizard digestive tract positively affected the germinability, mean germination time, emergence rate index and synchronization index of P. gounellei seed germination when compared with the control treatment (p < 0.05). The results indicated that T. semitaeniatus is an effective seed disperser of P. gounellei, as the funicular pulp of this species produces allelopathic substances that inhibit seed germination. Consequently, this lizard's participation as a dispersal agent is necessary to ensure the successful germination of the cactus. Highlights: Pilosocereus gounellei is a columnar cactus which fruit morphology suggests ornitochory as primary seed dispersal. The funicular pulp of P. gounellei produces allelopathic substances that inhibit the seed germination. The participation of a dispersal agent is necessary to ensure the successful germination of P. gounellei . Tropidurus semitaeniatus is an effective seed disperser of columnar cactus P. gounellei .